MARKETING ANALYSIS OF MEDICAL TOURISM IN INDIA - Manhas, Parikshat Singh; -, Ramjit (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2015)
The aim of the present research is to carry out the marketing analysis and to determine the potential of the medical tourism, to identify the various challenges to the medical tourism in India and to suggest and recommend the marketing strategies to develop the India as the medical tourism destination. The research is primarily based on the secondary sources by searching the various potential academic journals and reports potential articles, with medical tourism in the title, were assessed using EBSCO, UGC-Inflabanet, Google Search, and online library. The SWOT analysis, which really can be a backbone for the policy making helping in implementing the same in order to make India as a medical segment in the Indian Medical Tourism Industry.